(untitled) (Research, Society and Development, 2018)
This study aims to conduct an analysis of initiatives to prevent pressure injuries in adults hospitalized in Intensive Care Units, which have been published in the nursing literature. It is an integrative bibliographical review, from data collection 12 articles on national and international virtual bases of the last 10 years. Amongst the initiatives for the prevention of pressure injury, it was found that most of them are in the area of patient safety, mainly with the Braden, Glasgow and the International Patient Safety goals, guided by the World Health Organization. A still small number of studies that demonstrate other initiatives of prevention of this type of injury, besides the application of scales and protocols of classification and prevention of said adverse event are identified. In more recent articles, starting in 2013, educational and work process modeling actions are described, which lead to the adoption of a culture of patient safety and establish an indicator of quality at the health service as well as the degree of care of the nursing team.